Covid 19 and its Challenge on Muslim Prayers, a Discussion in The Light of Maqashid Asy-Syariah - Monsurat Abdussalam Al Haqiqi (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2020)
The Covid 19 Pandemic has thrown a fundamental challenge to the world, leading to engaging the stakeholders in rigorous research exercise and exposing the weakness in some current values system. As a safety measure, all forms of gathering were prohibited. Being a gathering place too, some mosques were closed while some were left open to observe congregational prayer in distance. This shows a disparity in scholars opinions as some scholars are clearly against this practice. This work is a comparative and maqashid based research, highlighting the two positions of scholars regarding this type of congregational prayer. In this study resulted that praying congregational prayer at home is better than praying in the mosque while observing distance for it is free from elements of doubt. To ensure prayer is perpetually observe in the sacred mosques, it is better for the mosque keeper to provide soap and water to be used before and after the prayer. They should also compel the use of face mask as it is more secure